Motywowanie pracowników w przedsiębiorstwach sektora spożywczego - Bombiak, Edyta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The article is an introduction of considerations of the Author on of the efficiency of workers motivate. One contained in him the test of the verification of the statement founding that the practical in firms tools of motivate are inadequate to expectations of workers, what unprofitable affects on the level of their engagement. The elaboration contains also fragments of results of researches on the group of food industry firms activity on the ground of the siedlecki administrative district